Effects of Air Temperature and Humidity on the Kinetics of Sludge Drying at Low Temperatures - Zhenyu Wang (MDPI AG, 2021)
In this study, a low-air temperature sludge drying system was constructed and the effects of temperature and relative humidity on the characteristics of the system were investigated. The results showed that the drying rate of sludge increased with an increase in air temperature and a decrease in the air’s relative humidity. The influence of temperature on the average drying rate exhibited an approximate quadratic distribution, while the influence of relative humidity on the average drying rate exhibited an almost linear distribution. The relationship equations of the average drying rate, temperature, and humidity were summarized and compared with the experimental results, and the maximum relative error was 7.6375%. By comparing the experimental results with the commonly used thin-layer drying models, it was found that the sludge drying characteristics were more consistent with the Midilli model. Based on the relevant parameters of the Midilli model, the relationship between the segmented drying moisture content and the average drying rate was proposed, and the empirical formula of the drying rate and MR under different conditions was fitted.